Computational prediction for the formation of amides and thioamides in the gas phase interstellar medium - Mohamad Akbar Ali; Mohamad Akbar Ali; Sorakayala Thripati; Sorakayala Thripati (Frontiers in Chemistry)
Amino acids and amide bonds (−C(O)−NH−) are the essential components of proteins, which serve as the foundation of life on Earth. As a result, molecules containing peptide bonds are of great interest in studies related to the origin of life and are central to both terrestrial and prebiotic chemistry. Despite this, our understanding of how nitrogen-containing compounds like formamide and urea, along with their sulfur analogs thioformamide and thiourea, form in the cold interstellar medium (ISM) remains incomplete. The chemistry underlying their formation is largely elusive, making the elucidation of their mechanism in the ISM and EA a topic of ongoing interest. This study employs ab initio//density functional theory (DFT) calculations to predict the possible formation routes of amides and thioamides. The rate constants (k) for barrierless reactions were determined using statistical rate theory, such as microcanonical variational transition state theory (µVTST) and Rice–Ramsperger–Kassel–Marcus (RRKM)/master equation (ME) simulations, to understand their kinetic behavior. Using basic interstellar precursors—CO, CS, NH2, H2, and NH3—we assessed gas-phase formation routes for amides and thioamides. The data reveal that thioamides (HCSNH2, NH2CSNH2) may form under ISM conditions, while amides (HCONH2, NH2CONH2) are less likely due to their relatively high energy barriers (>5 kcal/mol). In this work, we suggest the potential detection of four new molecules in ISM environments based on enthalpy and rate constant calculations: (i) ·CSNH2, (ii) HCSN·H, (iii) HCSNH2, and (iv) NH2CSNH2. Furthermore, organosulfur-bearing molecules are identified as potential precursors to iron-sulfide grains and astrobiologically significant compounds, such as the amino acids methionine and cysteine. Understanding these mechanisms is crucial for linking the chemistries of carbon, nitrogen, oxygen, and sulfur in deep space, thereby expanding our knowledge of the sulfur cycle within the Galaxy.